From numbers to medical knowledge: harnessing combinatorial data patterns to predict COVID-19 resource needs and distinguish patient subsets - Satashia, Parthkumar H.; Franco, Pablo Moreno; Rivas, Ariel L.; Isha, Shahin; Hanson, Abby; Narra, Sai Abhishek; Singh, Kawaljeet; Jenkins, Anna; Bhattacharyya, Anirban; Guru, Pramod; Chaudhary, Sanjay; Kiley, Sean; et al. (Frontiers in Medicine, 2023)
Background: The COVID-19 pandemic intensified the use of scarce resources, including extracorporeal membrane oxygenation (ECMO) and mechanical ventilation (MV). The combinatorial features of the immune system may be considered to estimate such needs and facilitate continuous open-ended knowledge discovery. Materials and methods: Computer-generated distinct data patterns derived from 283 white blood cell counts collected within five days after hospitalization from 97 COVID-19 patients were used to predict patient's use of hospital resources. Results: Alone, data on separate cell types -such as neutrophils-did not identify patients that required MV/ECMO. However, when structured as multicellular indicators, distinct data patterns displayed by such markers separated patients later needing or not needing MV/ECMO. Patients that eventually required MV/ECMO also revealed increased percentages of neutrophils and decreased percentages of lymphocytes on admission. Discussion/Conclusion: Future use of limited hospital resources may be predicted when combinations of available blood leukocyte-related data are analyzed. New methods could also identify, upon admission, a subset of COVID-19 patients that reveal inflammation.